1996
DOI: 10.1093/schbul/22.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidity in Schizophrenia

Abstract: The extent and consequences of medical comorbidity in patients with schizophrenia are generally underrecognized. Patients with comorbid conditions are usually excluded from research studies, although they probably represent the majority of individuals with schizophrenia. Elderly patients are especially likely to have comorbid disorders. In this article, we review selected literature on medical comorbidity in schizophrenia, including physical illnesses, substance use, cognitive impairment, sensory deficits, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
213
2
13

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(230 citation statements)
references
References 110 publications
2
213
2
13
Order By: Relevance
“…On the one hand, it was shown that older patients with schizophrenia had significantly lower physical co-morbidity compared to patients with major depression (Lacro, Jeste, 1994;Adams & Ball, 2000); older schizophrenia patients report even fewer co-morbid physical illnesses than healthy comparison subjects (Jeste et al, 1996). Of course, it can be only a sign of the decreased attention to the physical symptoms, because illnesses in schizophrenic patients, if present, tend to be more severe (Jeste et al, 1996). However, it was shown (Goldman, 1999) that patients with schizophrenia are at decreased risk for certain disorders, such as rheumatoid arthritis and allergies.…”
Section: Psychosis and Search Activitymentioning
confidence: 99%
“…On the one hand, it was shown that older patients with schizophrenia had significantly lower physical co-morbidity compared to patients with major depression (Lacro, Jeste, 1994;Adams & Ball, 2000); older schizophrenia patients report even fewer co-morbid physical illnesses than healthy comparison subjects (Jeste et al, 1996). Of course, it can be only a sign of the decreased attention to the physical symptoms, because illnesses in schizophrenic patients, if present, tend to be more severe (Jeste et al, 1996). However, it was shown (Goldman, 1999) that patients with schizophrenia are at decreased risk for certain disorders, such as rheumatoid arthritis and allergies.…”
Section: Psychosis and Search Activitymentioning
confidence: 99%
“…Use of medical care often decreases after the onset of a psychiatric disorder (Jeste et al, 1996), and even when patients are engaged in healthcare services, rates of undiagnosed physical illnesses are often high . Other patient characteristics may also contribute to poor detection and diagnosis of physical illness such as impaired ability to verbalise concerns (Lieberman and Coburn, 1986;Massad et al, 1990), poor insight into illness (Massad et al, 1990), denial of illness (Goldman, 1999) or an unwillingness to consult a doctor other than their psychiatrist.…”
Section: Overcoming Barriers To Carementioning
confidence: 99%
“…Il existe une prévalence importante de DT2 chez les patients souffrant de schizophrénie et cette prévalence semble augmenter avec l'avancée en âge de ces patients [8,11,14]. Cette prévalence augmentée précéderait même l'utilisation généralisée des nouveaux neuroleptiques et serait indépendante du traitement [5,14].…”
Section: éPidémiologieunclassified